Comparative study on 3 oral potassium formulations for treatment of hypokalemia in dairy cows. (17th May 2019) - Wittek, Thomas; Müller, Anja Elvira; Wolf, Franz; Schneider, Stephanie
Abstract: Background: Hypokalemia is of clinical relevance in cattle. Different mostly empirical treatment options are suggested. Hypothesis/Objectives: To evaluate if oral administration of potassium influences the plasma concentration, the intracellular concentration in erythrocytes and in muscle, renal excretion of potassium, and to assess if there are differences in the efficacy of the potassium formulations. Animals: Thirty cows with hypokalemia (plasma concentration <3.5 mmol/L) were systematically allocated to 3 treatment groups (10 cows/group). Methods: The cows received 52 g of potassium in different formulations: group B—potassium chloride bolus (release over 12 hours); group G—potassium propionate gel (release over 2 hours); and group S—potassium chloride solution (immediately available). Potassium concentrations were repeatedly measured in plasma, erythrocytes, muscle, and urine using ICP‐OES. Results: Plasma potassium concentrations for all preparations increased within 30 minutes and the increase lasted for 12 hours. The concentrations of potassium in the erythrocytes and in the muscle, renal potassium excretion, and total urine volume were not affected by administration of any product. There were no differences between the treatments groups. The feed intake increased in 50% of cows within 2 hours after potassium application, which may contribute to the increase of plasma potassium concentration. Conclusions and Clinical Importance: All the studied potassium formulations are equally effective to treat hypokalemia in dairy cows for over 12 hours but do not influence intracellular concentration or renal excretion of potassium. The plasma potassium concentration should be reevaluated after 12 hours.